Definition of Lepidocyrtus lusitanicus Gama, 1964 species-complex (Collembola, Entomobryidae), with description of new species and color forms from the Iberian Peninsula - Mateos, Eduardo (Zootaxa, 2008)
Lepidocyrtus lusitanicus is one of the species with greater color pattern variability within the genus Lepidocyrtus. Four subspecies have been described in relation to its body color variation. The study of various populations of Lepidocyrtus from the Iberian Peninsula has allowed me to describe the new chromatic form L. lusitanicus form A, as well as the new species L. bilobatus, which is very closely related to L. lusitanicus, and also shows high color pattern variability. The high similarity among species L. lusitanicus, L. selvaticus and L. bilobatus sp. nov., the high color pattern variability of their populations, the overlapping geographical distribution of many studied populations, and the presence of three dorsal macrochaetae between trichobothria m2 and a5 of the second abdominal tergum, led me to define the group Lepidocyrtus lusitanicus species-complex. This group included the three abovementioned species with all of their color forms.